IMPORTANCE OF CFD IN THE DESIGN OF EFFICIENT AND SUSTAINABLE SOLAR DEHYDRATORS FOR FRUITS: A SYSTEMATIC REVIEW - Paucarchuco Soto , Joselin (2023)
Among the postharvest conservation mechanisms, solar dryers are reported as sustainable and appropriate conservation systems for fruits. This article summarizes recent advances, opportunities and challenges in solar fruit drying. Furthermore, the review analyzes the mathematical models commonly used for the evaluation, design and optimization of solar dryers. For the systematic review, databases (Scopus, Scielo and Science Direct) were used, following the PRISMA guideline, which helped carry out the bibliometric analysis and identify the most relevant articles from the last 5 years (25 articles analyzed). Vosviewer software was also used to visualize connections and maps of scientific knowledge. Highlighting the importance of simulation conditions, characteristics of mathematical modeling and construction materials in the design of more efficient and sustainable solar dehydrators. In addition, some specific results are mentioned, such as the thermal efficiency of an indirect solar dehydrator and optimal values ​​of temperature and humidity in a predictive model. Immense research results have also been produced using CFD based on heat and mass transfer at the micro level. Micro-level CFD modeling indicates that modeling and simulations were performed at the fruit level, without considering the performance of the solar dryer. However, the performance of a solar dryer has a huge effect on the speed and kinetics of drying and consequently determines the quality of the product.